การสำรวจวิธีการประมาณการค่าอำนวยการก่อสร้างในโครงการก่อสร้างอาคาร - กนกศักดิ์ โล่ห์สุวรรณ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The overhead cost is the important part of the construction project that we have not to neglect for the estimate price. if it is not enough it may be made the project to lose the money or over the estimate may be not bidding the project. This research is the part of the study of the overhead cost for the construction of the building by grouping the list of the overhead cost and the factor that affect to it. Including the list of overhead cost by survey and questionnaire and the record shows volume and price. There are variety ways to study but most of all we use the estimate from the information and period of work . The factors that will effect to the project are the place where the construction is the workers and officers. The average of the overhead cost budget is 7.21% of Industry Plant And Warehouse Construction Project. And cost budget is 15.68% of Department Store Convention Hall and Office Building Construction Project. It can be seen that the Construction characteristics of the building. It is estimated the director of the construction detail of the different type of the building construction. The most expense is depend on Electricity Supply and Electricity fee, equipment, tools machinery and the wages for work and officer and the safety. For all these expense cost half of the price whit we have to estimate the right price and we have to be carful for the expense during working